Influence of C4 null genes on infection with human immunodeficiency virus. Issue 6637 (11th June 1988) - Cameron, P U; Cobain, T J; Zhang, W J; Kay, P H; Dawkins, R L
Abstract : The hypothesis that complement is important in the host response to human immunodeficiency virus (HIV) was tested. Complement C4 and Bf allotypes were determined in 26 patients who fulfilled the diagnostic criteria for persistent generalised lymphadenopathy due to HIV, 72 homosexuals who were negative for antibody to HIV, and 185 control subjects drawn from the local population. HLA-A, B, and DR were also typed and the phenotypes examined for the presence of supratypes and C4BQ0. Eleven patients (42%) had C4B null alleles compared with only 13 (18%) homosexuals who were negative for antibody and 28 (15%) controls. From estimates of gene frequencies the difference between the patients with lymphadenopathy and the controls was significant after conservative correction. In the patients only a minority (six) of the C4B null alleles were contained within ancestral haplotypes. Together with the fact that C4 null alleles result in partial deficiency of C4, this finding suggests that products of complement genes are important in infection with HIV or its consequences, or both. A role is proposed for complement and Fc receptors.